TAZ stimulates exercise‐induced muscle satellite cell activation via Pard3-p38 MAPK-TAZ signalling axis - Kyung Min Kim; Gi Don Yoo; Woong Heo; Ho Taek Oh; Jeekeon Park; Somin Shin; Youjin Do; Mi Gyeong Jeong; Eun Sook Hwang; Jeong‐Ho Hong (Wiley, 2023)
Abstract Background Exercise stimulates the activation of muscle satellite cells, which facilitate the maintenance of stem cells and their myogenic conversion during muscle regeneration. However, the underlying mechanism is not yet fully understood. This study shows that the transcriptional co‐activator with PDZ‐binding motif (TAZ) stimulates muscle regeneration via satellite cell activation. Methods Tazf/f mice were crossed with the paired box gene 7 (Pax7)creERT2 mice to generate muscle satellite cell‐specific TAZ knockout (sKO) mice. Mice were trained in an endurance exercise programme for 4 weeks. Regenerated muscles were harvested and analysed by haematoxylin and eosin staining. Muscle tissues were also analysed by immunofluorescence staining, immunoblot analysis and quantitative reverse transcription PCR (qRT‐PCR). For the in vitro study, muscle satellite cells from wild‐type and sKO mice were isolated and analysed. Mitochondrial DNA was quantified by qRT‐PCR using primers that amplify the cyclooxygenase‐2 region of mitochondrial DNA. Quiescent and activated satellite cells were stained with MitoTracker Red CMXRos to analyse mitochondria. To study the p38 mitogen‐activated protein kinase (MAPK)-TAZ signalling axis, p38 MAPK was activated by introducing the MAPK kinase 6 plasmid into satellite cells and also inhibited by treatment with the p38 MAPK inhibitor, SB203580. Results TAZ interacts with Pax7 to induce Myf5 expression and stimulates mammalian target of rapamycin signalling for satellite cell activation. In sKO mice, TAZ depletion reduces muscle satellite cell number by 38% (0.29 ± 0.073 vs. 0.18 ± 0.034, P = 0.0082) and muscle regeneration. After muscle injury, TAZ levels (2.59‐fold, P < 0.0001) increase in committed cells compared to self‐renewing cells during asymmetric satellite cell division. Mechanistically, the polarity protein Pard3 induces TAZ (2.01‐fold, P = 0.008) through p38 MAPK, demonstrating that the p38 MAPK-TAZ axis is important for muscle regeneration. Physiologically, endurance exercise training induces muscle satellite cell activation and increases muscle fibre diameter (1.33‐fold, 43.21 ± 23.59 vs. 57.68 ± 23.26 μm, P = 0.0004) with increased TAZ levels (1.76‐fold, P = 0.017). However, sKO mice had a 39% reduction in muscle satellite cell number (0.20 ± 0.03 vs. 0.12 ± 0.02, P = 0.0013) and 24% reduction in muscle fibre diameter compared to wild‐type mice (61.07 ± 23.33 vs. 46.60 ± 24.29 μm, P = 0.0006). Conclusions Our results demonstrate a novel mechanism of TAZ‐induced satellite cell activation after muscle injury and exercise, suggesting that activation of TAZ in satellite cells may ameliorate the muscle ageing phenotype and may be an important target protein for the drug development in sarcopenia.